ONLINE PURCHASE DECISION MODEL FROM A TRUST AND EASE OF USE PERSPECTIVE IN THE ONLINE MARKETPLACE : (CASE STUDY AT TOKOPEDIA.COM) - Raihan Fajri Ramadhan; Rita Komaladewi; Asep Mulyana (Journal of Business Studies and Management Review, 2021)
This study aims to describe and examine the impact of Trust and Ease of Use through E-Commerce in Online Purchase Decision at Marketplace Online. The methodology design used in this research is quantitative research with a survey method, for an analysis tool used is multiple linear regression. The method used to attract the sample is non-probability in the form of purposive sampling with the main criteria of the sample that is Tokopedia.com users who have made transactions at least 1 time. The size of respondents used as many as 100 respondents. The results of the study found that there is a positive and significant result of the trust and ease of use variables on online purchasing decisions both partial and simultaneous. This can be explained that the main factors that consumers consider before conducting online purchasing activities are whether they trust the sites that provide these online services and trust the online sellers on the website to encourage and build long-term relationships with consumers. Second is the impact of the ease of use on purchasing decisions, which can be explained by the ease of use perceived by Tokopedia users will tend to provide a sense of comfort and ease that affects consumers' online purchasing decisions. Thus, the recommendation for Tokopedia.com is to put more concern on updating the user experience to make it more manageable for all users to remain to use Tokopedia.com. and to strengthen payment systems and complaint handling for both consumers and sellers.